Acute scoliosis as an unusual presentation of pneumonia: A case report. Issue 24 (June 2018) - Atwal, Rajan; Stewart, Charles
Abstract : Abstract: We describe the unique case of a child with pneumonia presenting with acute scoliosis and abdominal pain, without any typical features of the disease. A 10-year-old girl presented to the emergency department on 3 consecutive days with right-sided abdominal pain. There were no associated features, in particular, no fevers or respiratory symptoms. On the first 2 presentations, observation, examination, and blood test findings were unremarkable. Chest x-ray and abdominal ultrasound were also normal. On the third presentation a marked scoliosis was noted and abdominal examination revealed right-sided tenderness with rebound. The patient was admitted and a computed tomographic scan of the abdomen arranged. Unexpectedly, this revealed a right lower lobe pneumonia and associated pleural effusion. Despite treatment, the parapneumonic effusion enlarged rapidly and she developed respiratory distress, necessitating transfer to a tertiary centre. The diagnosis of pneumonia can be challenging because of a lack of respiratory signs, the masking of systemic features by antipyretic effects of first-line analgesics, and a high rate of false-negative chest radiographs. The development of acute scoliosis should lead the clinician to strongly consider pneumonia in such circumstances.